PENGARUH INTENSITAS MENONTON TAGLINE IKLAN SUZUKI LETâS TERHADAP MINAT BELI - Yuwarti, Harti (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2014)
Suzuki is the automotive company which has been recognized by the public. In order to maintain its presence in the market Suzuki did not want to miss with other companies in designing their products are mainly for the production of motorcycles. To introduce their products to the public many companies that advertise in the media, especially television companies in the business of making the competition getting tougher similar to win the heart of the community or the consumer. This requires the advertisers to be more creative in the ad serving the public interest and understand the message delivered so as to change the attitude towards the product being advertised. The research method using SOR theory using a quantitative approach, namely through research on the number of people using population, sample and literature. Results showed interest purchasing in Komplek Bukit Kencana Jati Makmur Pondok Gede is high.